2003
DOI: 10.1017/s0031182003003457
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic potential of autoclaved Leishmania donovani with BCG against experimental visceral leishmaniasis

Abstract: The prophylactic efficacy of autoclaved Leishmania donovani (ALD) and autoclaved L. major (ALM)--a heterologous vaccine developed against cutaneous leishmaniasis (used as a reference vaccine), along with BCG--was evaluated against L. donovani in hamsters (Mesocricetus auratus). Animals were immunized with triple doses (21 days apart) of either ALD or ALM (1.0 mg) with or without BCG (0.1 mg) and challenged 21 days later with 1 x 10(6) L. donovani amastigotes intracardially. Animals immunized with ALM + BCG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Also, the use of ALD as an adjuvant along with gp63?Hsp70 antigen significantly protected the BALB/c mice against Leishmania infection and reduced the parasite load by 85.7 %. This is in agreement to the studies which showed that vaccination with autoclaved L. major conferred significant protection in simian and mice (Dube et al 1998;Misra et al 2001;Michel et al 2006) while ALD has been shown to confer protection in hamster model (Srivastava et al 2003). Immunization with autoclaved Leishmania antigen has been shown to induce a significant resistance to challenge infection in mice as observed by reduction in parasite load (Nagill et al 2009).…”
Section: Discussionsupporting
confidence: 86%
“…Also, the use of ALD as an adjuvant along with gp63?Hsp70 antigen significantly protected the BALB/c mice against Leishmania infection and reduced the parasite load by 85.7 %. This is in agreement to the studies which showed that vaccination with autoclaved L. major conferred significant protection in simian and mice (Dube et al 1998;Misra et al 2001;Michel et al 2006) while ALD has been shown to confer protection in hamster model (Srivastava et al 2003). Immunization with autoclaved Leishmania antigen has been shown to induce a significant resistance to challenge infection in mice as observed by reduction in parasite load (Nagill et al 2009).…”
Section: Discussionsupporting
confidence: 86%
“…This particular aspect of macrophage effector function in the hamster is similar to the function of human macrophages, so this small animal model can be used as a tool to dissect the effect of this unique NOS2 gene regulation on disease phenotype. However, despite the relative IFN-␥ unresponsiveness of the NOS2 transcriptional unit in this animal, protection against systemic parasite challenge by prior skin infection or vaccination can be achieved (47)(48)(49)(50)(51). Most notably, in hamsters vaccinated with DNA encoding the KMP-11 Ag, protection against parasite challenge was associated with expression of NOS2 mRNA and NO production (47).…”
Section: Discussionmentioning
confidence: 93%
“…Keeping this in mind, various studies have been carried out with autoclaved L. major and L. donovani along with BCG or CpG oligonucleotides against cutaneous and visceral leishmaniasis in primates and murine models and encouraging results have been observed by many workers [79][80][81][82][83] that provide the basis for further human trials.…”
Section: Intermediate Protectionmentioning
confidence: 99%